Financial toxicity and strain among men receiving prostate cancer care in an equal access healthcare system. (17th October 2020) - Bauer, Alexandria G.; Jefferson, Melanie; Nahhas, Georges J.; Savage, Stephen; Drake, Richard; Lilly, Michael; Ambrose, Linda; Caulder, Susan; Mahvi, David; Hughes Halbert, Chanita
Abstract: Purpose: To examine financial toxicity and strain among men in an equal access healthcare system based on social determinants and clinical characteristics. Methods: Observational study among men receiving prostate cancer care ( n  = 49) at a Veterans Health Administration (VHA) facility. Financial hardship included overall financial strain and financial toxicity due to healthcare costs. Financial strain was measured with one item asking how much money they have leftover at the end of the month. Financial toxicity was measured with the Comprehensive Score for Financial Toxicity (COST) scale. Results: Comprehensive Score for Financial Toxicity scores among participants indicated moderate levels of financial toxicity ( M  = 24.4, SD = 9.9). For financial strain, 36% of participants reported that they did not have enough money left over at the end of the month. There were no racial or clinically related differences in financial toxicity, but race and income level had significant associations with financial strain. Conclusion: Financial toxicity and strain should be measured among patients in an equal access healthcare system. Findings suggest that social determinants may be important to assess, to identify patients who may be most likely to experience financial hardship in the context of obtaining cancer care and implement efforts to mitigate the burden for those patients. Abstract : The purpose of this study was to examine financial toxicity and strain among men in an equal access healthcare system based on social determinants and clinical characteristics. There were no racial or clinically related differences in financial toxicity, but race and income level had significant associations with financial strain. Social determinants should be assessed to identify patients who may be most likely to experience financial hardship in the context of obtaining cancer care in order to implement efforts to mitigate the burden for those patients.